An economic index of riskiness - Robert J. Aumann; Roberto Serrano (Brown University, Department of Economics, 2006)
Define the riskiness of a gamble as the reciprocal of the absolute risk aversion (ARA) of an individual with constant ARA who is indifferent between taking and not taking that gamble. We characterize this index by axioms, chief among them a “duality” axiom which, roughly speaking, asserts that less risk-averse individuals accept riskier gambles. The index is homogeneous of degree 1, monotonic with respect to first and second order stochastic dominance, and for gambles with normal distributions, is half of variance/mean. Examples are calculated, additional properties derived, and the index is compared with others in the literature.
Keywords: C00; C43; D00; D80; D81; E44; G00; 330; riskiness; risk aversion; expected utility; decision making under uncertainty; portfolio choice; Sharpe ratio; variance-mean ratio; value at risk; Risiko; Index; Erwartungsnutzen; Entscheidung bei Risiko; Theorie